Karabakh: the Unfinished War - A. Krylov (Международная аналитика)
The author of the article analyzes the present situation on the territory of the Karabakh conflict and the positions taken by the parties. These are based on a “package approach” (Armenia) and a “step by step approach” (Azerbaijan). The two approaches conflict with one another, which is the main reason why the negotiations under the OSCE Minsk Group fail. This makes the armed scenario of solving the problem likely. The author describes Russia’s policy, which seeks to prevent a new war in Karabakh by maintaining a comparable military-political balance of power. Given the situation, the main task of the OSCE Minsk Group and Russian diplomacy is to create effective mechanisms to prevent resumption of hostilities. International ceasefire monitoring will create conditions for resuming talks to achieve a comprehensive settlement of the Karabakh conflict. Otherwise, the Karabakh problem will continue cause international tension.